Market and entrepreneurial orientations model to increase product innovation of culinary micro small medium enterprises in Indonesia - Ernawati Fatimah, Siska; Juhaida Johari, Razana; Komara, Acep; Maulany, Soesanti (Edelweiss Applied Science and Technology, 2024)
The objective of the article is to examine how market orientation and entrepreneurial orientation within an organization might bolster product innovation capabilities. By exploring these connections, the research aims to present a more comprehensive understanding of the research model and bridge existing limitations. This study employed a quantitative associative with a proportional-clustered-random-sampling technique. Data were collected through a questionnaire survey involving 400 respondents representing micro, small, and medium enterprises (MSMEs) and used structural equation modeling (SEM) to test hypotheses. The results indicated a significant impact of market and entrepreneurial orientations on product innovation with market orientation having a more dominant effect on product innovation than entrepreneurial orientation. A strong market orientation shows business players can absorb market knowledge for product innovation. Thus, MSME owners must swiftly digest this market information to plan future product developments, especially since some product types change rapidly during the product life cycle. The findings also show that the entrepreneurial approach has a poorer influence on product creation in MSMEs due to the necessity for competencies and risk-taking that the organization lacks. The Ministry of Cooperatives and MSME can use this input to design targeted programs to help MSME owners and creativity and invention to make distinctive things while being highly impacted by market demands. With its findings, the study augments our understanding of the product innovation position in Indonesian MSMEs and, illuminates MSMEs owners' next steps to sustain the competitiveness and operationalization of their businesses.